2017
DOI: 10.1371/journal.pone.0171244
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity of hinokitiol against biofilm formation in fluconazole-resistant Candida species

Abstract: The aim of this study was to investigate the ability of hinokitiol to inhibit the formation of Candida biofilms. Biofilm inhibition was evaluated by quantification of the biofilm metabolic activity with XTT assay. Hinokitiol efficiently prevented biofilm formation in both fluconazole-susceptible and fluconazole-resistant strains of Candida species. We determined the expression levels of specific genes previously implicated in biofilm development of C. albicans cells by real-time RT-PCR. The expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
6
31
0
1
Order By: Relevance
“…Additionally, growth of all bacterial strains is completely inhibited at concentrations of ≤50 μg/mL. Furthermore, it has been reported that hinokitiol inhibits the growth of Candida albicans , the primary causative agent of candidiasis, with MICs of 1.6–10 μg/mL . These findings suggest that hinokitiol is a safe and effective agent and may be suitable for local administration to the mouth or throat.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, growth of all bacterial strains is completely inhibited at concentrations of ≤50 μg/mL. Furthermore, it has been reported that hinokitiol inhibits the growth of Candida albicans , the primary causative agent of candidiasis, with MICs of 1.6–10 μg/mL . These findings suggest that hinokitiol is a safe and effective agent and may be suitable for local administration to the mouth or throat.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, it has been reported that hinokitiol inhibits the growth of Candida albicans, the primary causative agent of candidiasis, with MICs of 1.6-10 μg/mL. 39,40 These findings suggest that hinokitiol is a safe and effective agent and may be suitable for local administration to the mouth or throat. However, many studies have reported that hinokitiol has cytotoxic effects on human and murine tumor cell lines.…”
Section: Discussionmentioning
confidence: 90%
“…In C. albicans, the Ras/cAMP/PKA pathway is also involved in the regulation of biofilm development, chlamydospore formation, susceptibility to antifungals, cell death and other aspects (Jain et al, 2003;Phillips et al, 2006;Yi et al, 2011;Wang et al, 2015;Bottcher et al, 2016;Kim et al, 2017). Biofilms are a collective of microbial cells that grow on biological or nonbiological surfaces and are encased in a matrix of exopolymeric materials.…”
Section: Roles Of the Ras/camp/pka Pathway In Chlamydospore Formationmentioning
confidence: 99%
“…The MTL-homozygous biofilms are majorly governed by the Ste11-Hst7-Cek1/2 MAPK cascade, while the MTL-heterozygous biofilms are controlled by the Ras/cAMP/PKA pathway (Yi et al, 2011). Several studies also demonstrate that some chemicals such as hinokitiol and baicalin affect the biofilm formation through the regulation of the expression of the Ras/ cAMP/PKA pathway components (Wang et al, 2015;Kim et al, 2017). Moreover, Tpk1 plays a key role in the development of biofilm and cell wall integrity and structure through the control of the expression of cell wall proteins (Fanning et al, 2012).…”
Section: Roles Of the Ras/camp/pka Pathway In Chlamydospore Formationmentioning
confidence: 99%
“…QSARанализ структуры соединений из группы 2-аминотропонов и их цитотоксической активности по отношению к нормальным (HGF и HPLF) и опухолевым (Ca9-22, HSC-2, HSC-3) клеткам показал, что последняя возрастает с увеличением длины метиленовой боковой цепи в молекуле [9]. У ряда исследованных трополонов в результате многочисленных исследований обнаружены противоопухолевые [10][11][12], антиоксидантные [13], антивирусные [14], антибактериальные [15; 16], противогрибковые [17; 18]…”
Section: структурная формула трополоновunclassified